“Lived religion” in Henry's Reformation: the evidence from mass books - Aude DE MÉZERAC-ZANETTI (E-REA)
Henry VIII’s break with Rome and the emergence of the Royal Supremacy as an organizing principle and key element of theological fabric of the Church in England in the 1530s required adjustments to worship practices and thus affected the daily lives of the clergy and laity alike in ways that have never been fully elucidated. Looking systematically at alterations made to service books in use during Henry VIII’s reign challenges the persistent belief that not much changed in religious practice under the reign of Henry and sheds light on the agency of parish priests and local communities in interpreting and enacting the royal supremacy. The lived religion framework highlights the anthropological functions of ritual and helps understand the ways in which worship was harnessed to gain support for the Henrician reforms but even more significantly this approach provides heuristic tools to examine the pragmatic function of alterations, revealing what they meant to the people who effected them and to lay men who were charged with the enforcement of these changes. This article argues that the royal supremacy was a key component of the lived religion of Henry's subjects.